1966
DOI: 10.1017/s0022112066000715
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mean and dynamic skin friction, separation and transition in low-speed flow with a thin-film heated element

Abstract: The application of a heated thin metallic film to the measurement of mean skin friction in laminar and turbulent flow on a flat plate, circular cylinder and in an annular tunnel is described. The manner in which transition and separation are detected with this instrument is illustrated by reference to tests on a circular cylinder. The influence of the ambient air temperature and the gauge temperature on the behaviour of the instrument is analysed and it is shown that a reliable element can be constructed, capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 4 publications
0
72
0
Order By: Relevance
“…measure skin friction has become a standard practice in turbulence research (Bellhouse and Schultz, 1966;Brown, 1967;Wallace et al, 1976;Blackwelder and Eckelmann, 1977;Sreenivasan and Antonia, 1977;Kreplin and Eckelmann, 1978). Related work has also been done using flush-mounted mass-transfer analogs of hot films Zilker and Hanratty, 1979).…”
Section: 0mentioning
confidence: 99%
“…measure skin friction has become a standard practice in turbulence research (Bellhouse and Schultz, 1966;Brown, 1967;Wallace et al, 1976;Blackwelder and Eckelmann, 1977;Sreenivasan and Antonia, 1977;Kreplin and Eckelmann, 1978). Related work has also been done using flush-mounted mass-transfer analogs of hot films Zilker and Hanratty, 1979).…”
Section: 0mentioning
confidence: 99%
“…Within this work Colella and Keith have accurately measured the shear stress on a surface piercing plate and concluded that it is not quite Gaussian in its distribution due to a skewness of 0.67. However, the voltage measurement of a hotfilm probe is not linearly related to the shear stress, [29,28]. When using constant temperature (CT) hot film transducers, the voltage measurement is a measure of the forced convection from interaction of the flow with the surface.…”
Section: Hotfilm Measurements As a Turbulent Quantitymentioning
confidence: 99%
“…They remarked that even a change in temperature of 0.1 ºC was significant. 34 The theory they presented indicated that conventional films are primarily sensitive to the difference between the film temperature and the temperature of the surroundings. Therefore, to study the thermal sensitivity of the films they simply altered the film temperature instead of the flow temperature.…”
Section: 248mentioning
confidence: 99%